Implementation of the Prefixspan Algorithm for Recommended Cinema Showings - Adellia Rahmasari; Dimas Adi Putra Pratama; Nisvy Sya`'bana Nugraha; Risnandy Maulana; Dinda Meysya Rochma (UIN Sunan Gunung Djati Bandung, 2021)
Along with technological developments that cause the amount of information available is also getting closer, at this time there are approximately 16.3 ZB data or the equivalent of one trillion GB. The purpose of this research is to see how the application of the Prefixspan algorithm for Sequential Pattern Mining (a method for obtaining an ordered pattern). The data used is Movie Meta Data in which there are several columns including genre, director, film etc. With this data, we purpose viewers to present recommendation films to be shown in theaters based on audience enthusiasm from the processed data.